2021
DOI: 10.1038/s41587-021-00989-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrating T cell receptor sequences and transcriptional profiles by clonotype neighbor graph analysis (CoNGA)

Abstract: Multi-modal single-cell technologies capable of simultaneously assaying gene expression and surface phenotype across large numbers of immune cells have described extensive heterogeneity within these complex populations, in healthy and diseased states. In the case of T cells, these technologies have made it possible to profile clonotype, defined by T cell receptor (TCR) sequence, and phenotype, as reflected in gene expression (GEX) profile, surface protein expression, and peptide:MHC (pMHC) binding, across larg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 69 publications
9
102
0
Order By: Relevance
“…We filtered out barcodes associated with nonunique cells or did not have a resolved CDR3 amino acid or nucleotide sequence. As previously reported (Schattgen et al, 2021), we found substantial non-specific binding in donor 1 and excluded this sample.…”
Section: Combined Tcr-seq/single-cell Rna-seq Data From Antigen-speci...supporting
confidence: 67%
“…We filtered out barcodes associated with nonunique cells or did not have a resolved CDR3 amino acid or nucleotide sequence. As previously reported (Schattgen et al, 2021), we found substantial non-specific binding in donor 1 and excluded this sample.…”
Section: Combined Tcr-seq/single-cell Rna-seq Data From Antigen-speci...supporting
confidence: 67%
“…To correct erroneous or missing dextramer assignments for individual cells within a clone we assign each T cell a specificity of the majority of cells from this clone. To measure the distance between TCR α/ÎČ clonotypes and plot logos for dominant motifs we used the TCRdist algorithm implementation and plotting functions from conga python package 58 . Sequence similarity network analysis and visualizations were performed with the igraph R package 59 and gephi software 60 .…”
Section: Tcr Repertoire Analysismentioning
confidence: 99%
“…TCR sequence matching was performed using the TCRdist algorithm as implemented in the Clonotype Neighbor Graph Analysis (CoNGA) python package's find_significant_tcrdist_matches function (https://github. com/phbradley/conga) (48). In this approach, the TCRdist score for a match is compared to a background distribution of TCRdist scores for the same TCRs matched to random TCR sequences generated using a probabilistic model of the V(D)J recombination process.…”
Section: Discussionmentioning
confidence: 99%